EXPLAINING THE ASSOCIATION BETWEEN ADOLESCENT PARENTING AND PRESCHOOLERS' SCHOOL READINESS: A RISK PERSPECTIVE. Issue 6 (8th July 2013) - Fagan, Jay; Lee, Yookyong
<x xml:space="preserve">Abstract</x> This study examined whether mother and father risk, child risk, family risk, and mother and father cognitive stimulation mediated the association between adolescent age status of co‐residential mothers and fathers and 48‐month child school readiness. Using the Early Childhood Longitudinal Study‐Birth cohort, it was found that the children of adolescent mothers and fathers scored lower on emerging literacy and math than those born to adult parents. The findings showed that individual mother and father cumulative risk and cumulative family risk at various times during early childhood partially mediated the associations between adolescent parent status and child outcomes as well as between young adult parent status and child outcomes. These findings indicated that multiple domains of risk, including father, mother, and family risk should be taken into account in order to gain a fuller understanding of the effects of adolescent parenting (and young adult parenting) on child outcomes.